Childfree Choices among Muslim Millennials: A Thematic Analysis of Social Factors and Islamic Legal Perspectives - Syifa Salsabila Saneva; Nurul A'la; Ghaitsha Nur Adilla; Muhammad Fadlan (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
The choice to live childfree has emerged as a growing lifestyle phenomenon among Muslim millennials, raising important social and religious debates within contemporary Muslim family life. This study aims to examine the social factors influencing childfree decisions and to analyze this phenomenon from the perspective of Islamic law, particularly through the framework of maqasid al-shari‘ah. Employing a qualitative case study approach, data were collected through in-depth interviews with Muslim couples who consciously chose to remain childfree and were analyzed thematically using NVivo 12 software. The findings reveal five primary factors shaping childfree choices: economic considerations, mental health and psychological readiness, personal life experiences, social pressure, and ecological awareness. From an Islamic legal perspective, the decision not to have children is generally viewed as inconsistent with the fundamental objectives of marriage, especially the preservation of lineage (hifz al-nasl). Nevertheless, Islamic law allows space for ijtih?d when such decisions are based on legitimate and contextually justifiable considerations and do not constitute a rejection of Islamic principles. This study contributes to the growing body of literature on Muslim family dynamics and offers a conceptual foundation for further research on changing family practices in the modern Muslim context.